2022
DOI: 10.1111/imj.15671
|View full text |Cite
|
Sign up to set email alerts
|

Timely goals of care documentation in patients with frailty in the COVID‐19 era: a retrospective multi‐site study

Abstract: Background: Older frail patients are more likely to have timely goals of care (GOC) documentation than non-frail patients.Aims: To investigate whether timely documentation of GOC within 72 h differed in the context of the COVID-19 pandemic (2020), compared with the pre-COVID-19 era (2019) for older frail patients.Methods: Multi-site retrospective cohort study was conducted in two public hospitals where all consecutive frail adult patients aged ≥65 years were admitted under medical units for at least 24 h betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Consequently, goals of care decisions for the frail and older patients are a significant risk factor for death and adverse outcomes, especially in the face of the current pandemic. 2,17,35 Our study found that frail patients with COVID-19, regardless of their treatment limitation status, were likely to die in hospital, had longer hospitalization and were less likely to be discharged home. A recent individual patient data meta-analysis found that triaging patients just based on their frailty status was not justified.…”
Section: Relationship To Previous Studiesmentioning
confidence: 64%
See 4 more Smart Citations
“…Consequently, goals of care decisions for the frail and older patients are a significant risk factor for death and adverse outcomes, especially in the face of the current pandemic. 2,17,35 Our study found that frail patients with COVID-19, regardless of their treatment limitation status, were likely to die in hospital, had longer hospitalization and were less likely to be discharged home. A recent individual patient data meta-analysis found that triaging patients just based on their frailty status was not justified.…”
Section: Relationship To Previous Studiesmentioning
confidence: 64%
“…Consequently, goals of care decisions for the frail and older patients are a significant risk factor for death and adverse outcomes, especially in the face of the current pandemic. 2 , 17 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations